Generation of a dual-color reporter mouse line to monitor spermatogenesis in vivo - Makino, Yoshinori; Inoue, Erina; Hada, Masashi; Aoshima, Keisuke; Kitano, Satsuki; Miyachi, Hitoshi; Okada, Yuki (Frontiers in Cell and Developmental Biology, 2014)
In vivo fluorescent imaging technique is a strong tool to visualize the various cellular events such as the proliferation, differentiation, migration, and a lineage tracing in living cells requiring no further experimental procedure such as immunostaining. During spermatogenesis, unique and dynamic histone exchanges occur. Since the timing and types of histone exchanges defines the particular stages of spermatogenesis, visualizing certain types of histones in testes is useful not only for researching specific histone dynamics, but also for monitoring the stages of spermatogenesis in vivo. In this study, we report the establishment of two transgenic (Tg) mouse lines expressing histone H4-Venus (H4V) and histone H3.3-mCherry (H33C) fusion proteins in testicular germ cells, and demonstrated their utility for monitoring germ cell development in vivo. Because of the choice of promoter as well as the nature of these histones, H4V and H33C were exclusively expressed in the germ cells of the distinct stages, which allowed the determination of spermatogenic stages in real time. In addition, disappearance of H4V and H33C at particular stages of differentiation/fertilization also represented dynamic histone removal. Collectively, these Tg mice are a valuable resource not only for monitoring differentiation stages, but also for studying the chromatin dynamics of post-natal testicular germ cell development in vivo.